System Balance of the Russian Economy: Regional Perspective - Kleiner, Georgy Borisovich; Rybachuk, Maksim Aleksandrovich (Economy of Regions, 2019)
Balance is one of the economics’ cornerstone concepts. Researchers identify various types of balance, including commodity-money, industry, territorial, inter-period, etc. The universal representation of socio-economic systems in the form of a complex of object-oriented, project-oriented, environment-oriented and process-oriented systems enables to question the system balance, i.e., whether the scales of these subsystems are proportionate in the system. Furthermore, the concept of a system balance of the economy of the Russian Federation subjects, federal districts and the country as a whole appears. The paper aims to quantify the system balance of each subject and determine the current ratio of systemically balanced and unbalanced Russian subjects. The application of these correlations in the development of the Russian Federation’s socio-economic strategy will allow the increase of the socio-economic space’s connectivity. Moreover, it will impact the socio-economic policy’s continuity and targeting over time and the national economy’s sustainable development. Based on the provisions and methods of system economic theory, we evaluated the system balance of the Russian economy from a regional perspective. We calculated system balance index of the Russian Federation subjects, federal districts and the country as a whole. Then we identified groups of the Russian Federation subjects of with a high, medium and low degree of system balance. Further, we investigated the dynamics of the structure of groups of regions-leaders and regions-outsiders according to the degree of system balance for the period from 2012 to 2016. We created the heat map of the Russian economy’s system balance from a regional perspective. Finally, we created the guidelines for the system economic policy for territorial development, aimed at increasing the number of system balanced regions. The article justifies the need to include a section reflecting the proportions between the development of the object-oriented, environment-oriented, process-oriented and project-oriented subsystems of the region in the strategy of the Russian Federation subjects.